Perceived Irishness : the (re)construction of 'Irish' identity within the continuum of liquid modernity - BouAynaya, Yaqoub (Trinity College (Dublin, Ireland). Department of Sociology, 2016)
This research explores perceived Irishness and to what extent identity in Ireland is reconstructed within the continuum of an ever changing society. It examines how values associated with identity affect the ways in which individuals participate in their perceived social reality, are perceived by ‘others’ and are re/presented between the collective local, national, European and global level. Thus, this thesis considers the evolution and maintenance of nationalism and relates this to the development of the postcolonial Irish nation state within the context of European governance and globalization. The methodology takes a multiphase approach that seeks to explore individuals’ perceived sense of identity, either in stability or flux, by exposure to variations of Irishness through the viewing of a multimedia presentation. This novel and innovative qualitative design relies on an audio-visual production made from one-to-one interviews with four individuals of differing backgrounds but who are all Irish citizens. By showing it to eight focus groups the ambition is to elicit in participants the deconstruction of ‘Irish’ national identity. Through focus group discussions on identity, ethnicity and citizenship evidence emerges from the transcribed and thematically analysed conversations. Consequently, in exploring the processes of socially constructing Irishness, this research facilitates insight into the processes which affect an individual’s self-understanding and social categorization. Such a reflexive social investigation reveal findings that substantiate an identity theory positing explicit contradictions between individuals’ reliance on deep-rooted and inherent notions of Irishness in contrast with awareness and a contemporary understanding of identity as being constructed through social experience. Furthermore, through empirical validation it postulates the socio-psychological process of ‘perceived rational pragmatism’ as the means by which individuals within ordo-liberal liquid modernity perceive of themselves as rational liberated beings. Through reflection, theory synthesis and the embedded agential design, this thesis informs the reconceptualization of contemporary ‘Irish’ identity. Its admissions seek to expedite an alternative re-imagination of, "what it means to be Irish" so as to better complement the aspirations towards an egalitarian based socio-democracy.
Keywords: Sociology, Ph.D.; Ph.D. Trinity College Dublin